A Common R219K Variant of ATP-Binding Cassette Transporter A1 Gene Alters Atherometabolic Traits in Pregnant Women With Gestational Diabetes Mellitus - Tang, Fangmei; Guan, Linbo; Liu, Xinghui; Fan, Ping; Zhou, Mi; Wu, Yujie; Liu, Rui; Liu, Yu; Liu, Sixu; Li, Dehua; Bai, Huai (Frontiers in Endocrinology, 2021)
Background: ATP-binding cassette transporter A1 (ABCA1) has important roles in high-density lipoprotein (HDL) metabolism and reverse cholesterol transport, and is implicated in lipid-related disorders. Genetic variants are involved in the pathogenesis of gestational diabetes mellitus (GDM). The objective of this study was to investigate the association of rs2230806 (R219K), a single nucleotide polymorphism (SNP) in the lipid-related gene, with the risk of GDM and related traits. Methods: The SNP, rs2230806, was genotyped, and clinical and metabolic parameters were determined in 660 GDM patients and 1,097 control subjects. Genetic associations with related traits were also analyzed. Results: The genotype distributions were similar in GDM patients and normal controls. However, significant differences in the variables examined in the study subjects were noted across the three genotypes. The genotype at the rs2230806 polymorphism was significantly associated with HDL-cholesterol (HDL-C) levels and atherogenic index (AI) values in GDM patients and total cholesterol (TC) and low-density lipoprotein-cholesterol (LDL-C) levels in control subjects. Subgroup analysis showed that the polymorphism was associated with diastolic blood pressure, in addition to HDL-C levels and AI, in overweight/obese GDM patients, while it was associated with TC levels, AI, pre-pregnancy body mass index (BMI), and BMI at delivery in non-obese GDM patients. In addition, this polymorphism was associated with TC, LDL-C, and apoB levels in overweight/obese control subjects. Conclusions: The rs2230806 polymorphism in the ABCA1 gene was associated with variations in atherometabolic traits in GDM patients, with characteristics of BMI dependency, but not with GDM. Our findings highlight a link between related phenotypes in women with GDM and genetic factors.